Translating Similes: a Comparative Perspective on Romanian Versions of the Novel Alice’s Adventures in Wonderland, by Lewis Carrol - Gabriela ȘAGANEAN (Philologia)
The article aims at emphasizing the role of simile in the literary work as a powerful stylistic device that enhances the image, emotional depth and significance of the text. Various functions of simile are presented, including its ability to create vivid visual impressions, to facilitate comparisons for a clearer understanding and to arouse an emotional resonance while reading literary texts. Different types of similes such as explicit/implicit, brief/extended, genuine/trite ones contribute uniquely to the narrative style and tone of the text. In addition, the work examines the challenges encountered in rendering similes in translation, focusing particularly on the difficulties encountered when they are transferred from English into Romanian and providing strategies for rendering them efficiently in translation. The comparative analysis of two translations highlights the complexity of translating similes, retaining their stylistic and emotional power and underlining the importance of cultural sensitivity and linguistic creativity in the translation process.